Penggunaan Google Spreadsheet untuk Meningkatkan Mutu Pendidikan di Sekolah Dasar: Utilizing Google Spreadsheet to Enhance Educational Quality in Primary Schools - Dantika, Fina Azizah; Aliyah, Adah (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
The use of information technology in education management is becoming increasingly important to improve efficiency and transparency in school management. This research aims to explore the implementation of Google Spreadsheet as a management information system at Al Kenzie Elementary School and analyze its impact on administrative effectiveness and parental involvement in learning. This research uses a qualitative approach with a case study design, where data is collected through in-depth interviews, observations, and documentation studies, then analyzed thematically. The results showed that Google Spreadsheet plays a role in improving the efficiency of recording and reporting academic data and school administration. However, the research also found the main obstacles in the implementation of this technology, namely the limited competence of human resources and the lack of policy support. The implications of this study emphasize the need for training strategies for education personnel as well as the development of more comprehensive technology adaptation policies in educational institutions. The findings contribute to the literature on digitalization in education, particularly in Islamic-based schools, and provide insights for policy makers in designing innovative strategies to improve the quality of education management.